PENGEMBANGAN SIWS (SISTEM INFORMASI WEB SEKOLAH) SMA DHARMA WANITA 4 TAMAN, SIDOARJO - Sumartono; Syaiful Hidayat; Boedi Martono (Penerbit LPPM- STKIP PGRI Bangkalan, 2020)
SMA Dharma Wanita 4 Taman, Sidoarjo is a private school, on Jalan Kalijaten 1B Taman, Sidoarjo already has a web of the results of community service collaboration conducted in 2019. As an educational institution, adequate information facilities are needed in accordance with the demands of the times. After reviewing, some features and the existence of a quality web requires development so that more optimal function. Methods: brainstorming, observation, conducting training to develop and manage web content and features, providing remote assistance (due to large-scale social restrictions / PSBB), and remote evaluation. The result is that all web administrators can manage the development of features that have been added. The new features added are the survey column, advertising column, and e-learning feature.